PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH - Priscilia Grace Bay; Maria Elerina Douk Tunti (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2019)
This study aims to examine the effect of the government's internal control system on the effectiveness of regional financial management and the influence of human resources competencies on the effectiveness of regional financial management. This study uses a purposive sampling method. The sample in this study was the Head of Subdivision, District Head, Sub-Head of Subdivision, and Staff of the Regional Financial Institutions (ASN) of the Kupang Financial Region. The sample used in this study was 45 respondents, where data was collected through a distributed questionnaire. The analysis is based on respondents' answers obtained through questionnaires distributed by researchers. The data analysis technique uses multiple linear regression analysis with the help of SPSS 21 program. The results of the study show that there is an influence between the Government’s Internal Control System on the Effectiveness of Regional Financial Management and there is no influence of Competency Human Resources on the Effectiveness of Regional Financial Management.